Correction to: First report of Theileria annulata in Nigeria: Findings from cattle ticks in Zamfara and Sokoto States - Adamu Haruna Mamman; Vincenzo Lorusso; Babagana Mohammed Adam; Goni Abraham Dogo; Kevin J. Bown; Richard J. Birtles (Parasites & Vectors, 2021)
An amendment to this paper has been published and can be accessed via the original article.